IL CANONE DI POLICLETO - Massimiliano Papini (Lexicon Philosophicum)
Polykleitos, sculptor sophos, after the archaic volumina drawn up by the architects on individual buildings, is the first author who engaged in a theoretical activity, by writing a work entitled Canon, in all likelihood in the mid-5th c. BC. Throughout the centuries, this work circulated widely among erudites across different fields: one can find a few ‘quotations’ and paraphrases of it in authors of the early Hellenistic age. According to Chrysippus’ testimony, transmitted by Galen, Polykleitos first wrote this work and then tested his theories by crafting a statue, to which he gave the same title as his treatise, Canon. The paper focuses on a critical analysis of all this evidence in order to address several controversial points concerning Polykleitos’ oeuvre, including the identification of the statue entitled Canon with a lost bronze archetype transmitted by many marble replicas, and which has traditionally been seen to coincide with the well-known Doryphoros. The last part of the article is devoted to a comparison between Polykleitos and Lysippos based on the ancient sources. The two great sculptors are more or less explicitly mentioned in some epigrams in the section about the andriantopoiika by the Hellenistic poet Posiddipus of Pella (as revealed especially by the new anthology discovered in a Milanese papyrus), who set them in contrast to one another. In the Hellenistic period a new canon was introduced: the canon of truth.